From Green Dynamic Capabilities to Competitive Advantage: A Dynamic Capabilities Perspective on Sustainability Innovation - Ruojun, Qi (International Review of Management and Marketing, 2026)
Drawing on the Dynamic Capabilities View (DCV), this study examines how green dynamic capability (GDC) drives green competitive advantage (GCA) in the hospitality sector through sustainability exploitation innovation (SEI) and sustainability exploration innovation (SER), and how environmental regulation (ER) moderates these relationships.Using survey data from 428 four- and five-star hotels in China, structural equation modelling with partial least squares was employed to test the proposed framework. Both SEI and SER significantly mediate the relationship between GDC and GCA. ER exerts a differential moderating effect: high-intensity ER strengthens the impact of SER, while low-intensity ER amplifies SEI’s influence. These results show that aligning innovation strategies with the regulatory environment maximizes the value of green capabilities. This study distinguishes the roles of two innovation modes in translating dynamic capabilities into competitive advantage. It clarifies ER’s nuanced moderating role, offering guidance for managers and policymakers aiming to enhance green innovation in the hospitality sector.